Clinical profile and outcome of neonates admitted in sick newborn care unit with hypernatremic dehydration and association with breastfeeding in a tertiary care hospital in Northern India - Bajaj, Mohit; R., Chiranth; Mahajan, Swati; Chauhan, Pancham (International Journal of Contemporary Pediatrics, 2021)
Background: Neonatal hypernatremic dehydration is a very commonly seen potentially devastating condition. Inadequate breastfeeding, gastrointestinal losses, warm weather and improperly diluted mixed feeding are the main etiologies linked with neonatal hypernatremic dehydration. We conducted this study to evaluate the etiology, risk factors, clinical symptoms and outcomes of neonates admitted with hypernatremic dehydration and its association with breastfeeding from hilly region in northern India. Methods: The authors retrospectively studied records from extramural sick newborn care unit (SNCU) from April 2018 to June 2019. Inclusion criteria for the study included admitted neonates with documented hypernatremia (serum sodium level >145 mmol/L). Results: Nine hundred and twenty-two neonates were admitted in sick newborn care unit during this study period. One hundred and three (13.39%) newborns were admitted with hypernatremic dehydration at the time of admission. All newborns had deranged kidney function tests at time of admission. Most commonly found presenting complaints were poor feeding (85.71%), fever (45.71%), loose stools (42.8%) and decreased urine output (8%). The mean (SD) sodium on admission was 154.04 (7.41) meq/L. The mean (SD) time taken to correct hypernatremia was 35.6 (14.6) hours. Six of total admitted newborn developed neurological complications (2 had developed cerebral venous thrombosis and 4 had developed seizures). Mortality rate was 4.4%. Top fed neonates (50.41%) had higher percentage of mean sodium level and acute kidney injury at time of admission. Conclusions: Hypernatremic dehydration is preventable and treatable condition. Looking in to and addressing etiology in a timely manner is main step in management. All mothers should be taught correct breastfeeding technique. More breast examination during prenatal and postnatal periods and careful neonatal weight record postnatally could decrease the incidence of neonatal hypernatremic dehydration. Top feeding should be discouraged and only exclusive breastfeeding for 6 months.